Fatores de risco cardiovascular em idosos que vivem na comunidade: análise de sobrevida - Sousa, Thais Vilela de (2019)
INTRODUCTION: The already deflagrated aging population process has contributed to changes in the causes of mortality worldwide influencing the increase of chronic noncommunicable diseases. Among the elderly, cardiovascular diseases (CVD) are the main group of chronic diseases because it is the leading cause of death in this population. The presence of cardiovascular risk factors (CVRF) impacts the morbidity and mortality of these individuals increasing the risk for cardiovascular events promoting pathological aging and death. Factors such as smoking, alcohol consumption, hypertension, dyslipidemia, diabetes mellitus, obesity and physical inactivity contribute to the reduction of survival in this population. OBJECTIVE: To analyze the relationship between cardiovascular risk factors and survival of elderly people living in the community over a 10-year period. METHOD: Survival analysis in a prospective cohort with 418 community-dwelling older adults living in the urban area of ​​Goiânia. They were evaluated at baseline in 2008 for sociodemographic characteristics (gender, color, age, marital status and social class), clinical (hypertension, systolic and diastolic blood pressure, diabetes mellitus, glycated hemoglobin, fasting glucose, dyslipidemia, low density lipoprotein, high density lipoprotein, body mass index and waist circumference) and lifestyle (physical activity level, smoking and alcohol consumption). After 10 years of follow-up, in 2018, the elderly survivors and those who died were compared and the groups of survivors compared to those who died from CVD and other causes according to the presence of CVRF to identify variables associated with CVD death. Associations were estimated by Pearson chi-square test, Student t test, ANOVA and Bonferroni tests. Survival was estimated at two, four, six, eight and 10 years by the Kaplan Meier method and the Logrank test and considering the significance level of 5%. Cox regression was performed to verify factors associated with survival time and to estimate the risk of death from CVD expressed as Hazard Ratio (HR) with a 95% confidence interval. RESULTS: Most of the elderly were female (66.0%), white (46.4%), married (54.8%) and with low education (3.4 years of schooling), predominantly hypertensive (81.6 %), irregularly active (44.0%) and former smokers (43.3%). The main risk factors for death from CVD were: age (HR: 1.067 CI: 1.027-1.1009), hypertension (RH: 3.178 CI: 1.144-8.826) and smoking (RH: 2.235 CI: 1.253-3.987). Being sedentary was a risk factor for reduced survival, increasing the odds of death 2.4 times. CONCLUSION: Factors such as older age, being hypertensive, smoker at some point in life and sedentary were risk factors for death from CVD. This study provided insight into the cardiovascular risk of aging over a ten-year period. Research is recommended to clarify not only the relationship between CVRF and mortality, but also to develop better interventions that reach this population resolutely, providing quality aging and autonomy.